Bridging the gap: a new approach to student academic support at the University of Exeter - Nicky King; Jess Johnson; Hannah Jordan; Hannah Lyons (Journal of Learning Development in Higher Education, 2025)
A review carried out during the spring of 2023 identified a need for a new approach to student academic support at the University of Exeter. The model places pastoral mentors within departments to bridge the ‘third space’ gap between academic and professional services student support. For students who are struggling or starting to struggle, they connect the various strands of support systems that can be overwhelming and become a known friendly and non-judgemental advocate within their department who can make a real difference to their ability to succeed in their studies. Implementing a rapid rollout of these third space roles is not without challenge with quantitative indicators of success some way off and well-documented financial issues resulting in universities having to prioritise scarce resources. However, by sharing the experiences of our pastoral mentors to date, we aim to demonstrate how these third space roles, with the focus, expertise, and capacity to look at the whole student experience, can make a tangible difference to student engagement, progression, and outcomes.